2010
DOI: 10.1016/j.cell.2010.10.033
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase II Subunits Link Transcription and mRNA Decay to Translation

Abstract: Little is known about crosstalk between the eukaryotic transcription and translation machineries that operate in different cell compartments. The yeast proteins Rpb4p and Rpb7p represent one such link as they form a heterodimer that shuttles between the nucleus, where it functions in transcription, and the cytoplasm, where it functions in the major mRNA decay pathways. Here we show that the Rpb4/7 heterodimer interacts physically and functionally with components of the translation initiation factor 3 (eIF3), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
209
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(221 citation statements)
references
References 62 publications
9
209
0
Order By: Relevance
“…There is also evidence that nuclear and cytoplasmic mRNA metabolism are linked. The Pol II subcomplex Rpb4/7 shuttles between the nucleus and cytoplasm (Selitrennik et al 2006) and is involved in transcription (Edwards et al 1991) and mRNA translation and degradation (Lotan et al 2005;Lotan et al 2007;Harel-Sharvit et al 2010). The Ccr4-Not complex is involved in mRNA degradation (Tucker et al 2002) and also in transcription (Liu et al 1998;Collart 2003;Collart and Timmers 2004;Kruk et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that nuclear and cytoplasmic mRNA metabolism are linked. The Pol II subcomplex Rpb4/7 shuttles between the nucleus and cytoplasm (Selitrennik et al 2006) and is involved in transcription (Edwards et al 1991) and mRNA translation and degradation (Lotan et al 2005;Lotan et al 2007;Harel-Sharvit et al 2010). The Ccr4-Not complex is involved in mRNA degradation (Tucker et al 2002) and also in transcription (Liu et al 1998;Collart 2003;Collart and Timmers 2004;Kruk et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA is then decapped and degraded by exonucleases from both ends. Despite the spatial separation of mRNA synthesis and translation/degradation, there is evidence that these processes are coordinated (Lotan et al 2005;Lotan et al 2007;Harel-Sharvit et al 2010).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…The same group reported that cytoplasmic mRNA decay is accelerated by association with a subcomplex of RNA pol II. This subcomplex, Rpb4/7, shuttles with mRNAs between the nucleus and cytoplasm, thus apparently linking transcription with mRNA stability (65)(66)(67)(68). Another study reported that glucose sensing involves coordinated transcriptional repression and mRNA decay (69).…”
Section: Snf1 May Inhibit Transcription At Amentioning
confidence: 99%
“…22,23 Another regulatory connection between transcription and mRNA decay, but in the direction from nucleus (transcription) to cytoplasm, has also been established since mRNAs can be co-transcriptionally bound by factors that imprint them and influence their stability and translatability. 24,25 The disruption of the mechanistic coupling between transcription and mRNA degradation helps to explain the regulation of the mRNAs that do change with growth (Fig. 1B).…”
Section: Levels Of Mrnas Of Specific Gene Functional Categories Corrementioning
confidence: 99%